168 International Study of Intracranial Aneurysm Embolization Using the Woven EndoBridge (WEB) Device: Results of the WorldWideWEB Consortium. (1st April 2022) - Adeeb, Nimer
Abstract : INTRODUCTION: Pooled data from several registries have shown satisfactory efficacy of the WEB device to treat wide-neck aneurysms. The present study is the most extensive multi-center collaboration that endeavors to investigate the angiographic and clinical outcomes of real-world treatment of intracranial aneurysms with the device. METHODS: The World-Wide-WEB consortium is a retrospective multicenter collaboration of international centers with no limitation on aneurysm location or rupture status. Both bifurcation and sidewall aneurysms were included. Angiographic and clinical outcomes and complications were assessed among all consecutive patients along with determinants of adequate aneurysm occlusion (i.e. complete occlusion or neck remnant). RESULTS: The cumulative population comprised 674 patients (median age 61.3 years; 71.3% female) with 686 intracranial aneurysms. MCA bifurcation (30.2%) was the most common location. Adequate occlusion was observed in 85.7% of aneurysms at the last follow-up. Aneurysm retreatment was required in 7.9% of aneurysms. Thromboembolic complications were encountered in 7.6% of patients, but only 2.0% had permanent neurological deficits, while 3.1% had hemorrhagic complications. We identified subarachnoid hemorrhage, immediate remnant aneurysm (as compared to complete occlusion), and minor compaction or major compaction (as compared to no compaction) as significant determinants for lower rates of adequate aneurysm occlusion on last follow up (p < 0.01). CONCLUSION: This report suggests an adequate efficacy and safety profile of the WEB comparableto the currently availablesurgical andotherendovascular techniques fortreatment ofintracranial aneurysms.